A Chief Operating Officer's Perspective on Managerial Coaching. Issue 4 (November 2022) - Carvalho, Charles; Carvalho, Sheldon; Carvalho, Fallan Kirby
The Problem: In recent years, managerial coaching has garnered increasing attention from organizations, even though practitioners suggest that managers may resist coaching employees. More dialog and research that uncovers the motivations, challenges, and benefits managers accrue from coaching, and the crucial role line and human resource development (HRD) managers can play in creating coaching cultures seems warranted. The Solution: Perspectives on actions that HRD practitioners can take to support managerial coaching are gained from an interview with a global organization executive. The Stakeholders: This article will benefit HRD practitioners and line managers seeking to institutionalize a culture of coaching.